Composting urban organic waste into agricultural inputs: Balangoda, Sri Lanka - Gianfelici, F.; Lançon, L.; Bucatariu, C.; Dubbeling, Marielle; Santini, G.; Fernando, Sudarshana (2016)
As in other cities of Sri Lanka, solid waste management has been a key problem in and concern for Balangoda Urban Council. Waste accumulations in the city have caused many problems, including unpleasant odours, contamination of water bodies, and contamination of paddy fields, giving rise to epidemic diseases such as Salmonella, typhoid fever, and diarrhoea. A Balangoda compost plant has been set up to process municipal solid waste into compost. The project started in 1999 as a city service to provide a solution to the solid waste problem, but converted into a business in later years. Integrated waste management in Balangoda now consists of a Municipal Solid Waste compost plant, septage treatment plant, plastic pelletiser and an open dump. In addition, as there is increasing awareness of environmental and health risks related to the use of agro-chemical fertilisers, demand for alternative – organic – fertilisers is increasing. As per the majority of the compost plants in the country, the Balangoda plants are located in semi-urban or rural areas, facilitating reuse of waste in agriculture, with farming areas located near the compost plants. The Balangoda system thus operationalises rural-urban linkages through the collection of urban food and organic waste and its recycling, sale, and reuse as compost for rural (and peri-urban) producers.